Foreign Aid and Economic Growth in Nepal - Jnawali, Sanjay; Gyanwaly, Ram Prasad (Janabhawana Research Journal, 2025)
This study focuses on conducting an empirical investigation to analyze the nature, trend, and structure of foreign aid and its impact on Nepal's economic growth. To achieve this, the study adopts descriptive and quantitative research design and utilizes an Autoregressive Distributed Lag model within the Barro regression framework. Data for the analysis, spanning from 1975 to 2021, are sourced from the Nepal Rastra Bank, Central Bureau of Statistics, and Ministry of Finance. The nature and trend analysis indicate that foreign aid follows a non-linear pattern, with an overall upward fluctuating trend across diverse sectors. The estimated results show that a 1 percent positive increase in foreign aid leads to a 0.22 percent rise in GDP in the long run, and a 0.09 percent increase in GDP in the short run, both at the 1 percent significance level. These findings indicate that foreign aid has a positive impact on Nepal's economic growth, contributing capital for investment in developing countries, and being more effective when macroeconomic indicators improve, leading to a more favorable economic situation. In the short run, foreign aid positively affects GDP due to effective monitoring, improved aid management, and focus on need-based sectors for development. The study concludes that Nepal needs to review its policies to address the growing trade deficit and closely monitor foreign aid for achieving higher economic growth.